SOSIALISASI KESELAMATAN DAN KEAMANAN ARUS LALU LINTAS PELAYARAN PADA ALUR PERAIRAN PT.WMI BIAK - Dominggus Rudolf Leiwakabessy; Andy Sahat Maasi Sigalingging; Djamil Hasim; Rijal Rijal (LPPM Universitas Bina Bangsa, 2024)
Safety and security of shipping traffic flow is an important aspect in maintaining safe and efficient maritime activities. However, the practice of arbitrarily setting up trawlers or fish catchers in the waterway area traversed by PT WMI Biak ships is faced with serious challenges that can interfere with shipping safety and security. To overcome this problem, a service initiative was conducted through the means of disseminating information or conducting educational sessions by involving resource persons from the Syahbandar and Port Authority Office (KSOP) and the Water and Air Police (Polairud) as well as 30 respondents. Through a series of socialization activities, the surrounding community was given a comprehension of the significance of adhering to safety and security regulations regarding maritime traffic flow. The results showed that there was a question and answer discussion by the community with the resource person on the risk of arbitrary trawling or fishing practices in the waterway, as well as reducing the potential for disruption to shipping activities. This makes if this socialization attracts community interest in contributing to creating a safer, more orderly and sustainable water environment for all parties involved in maritime activities